Age- and Sex-Dependent Changes in Androgen Receptor Expression in the Developing Mouse Cortex and Hippocampus. (3rd February 2015) - Tsai, Houng-Wei; Taniguchi, Saori; Samoza, Jason; Ridder, Aaron
Abstract : During the perinatal period, male mice are exposed to higher levels of testosterone (T) than females, which promotes sexual dimorphism in their brain structures and behaviors. In addition to acting via estrogen receptors after being locally converted into estradiol by aromatase, T also acts directly through androgen receptor (AR) in the brain. Therefore, we hypothesized that AR expression in the developing mouse cortex and hippocampus was sexually dimorphic. To test our hypothesis, we measured and determined AR mRNA and protein levels in mouse cortex/hippocampus collected on the day of birth (PN0) and 7 (PN7), 14 (PN14), and 21 (PN21) days after birth. We demonstrated that, as age advanced, AR mRNA levels increased in the cortex/hippocampus of both sexes but showed no sex difference. Two AR proteins, the full-length (110 kDa) and a smaller isoform (70 kDa), were detected in the developing mouse cortex/hippocampus with an age-dependent increase in protein levels of both AR isoforms at PN21 and a transient masculine increase in expression of the full-length AR protein on PN7. Thus, we conclude that the postnatal age and sex differences in AR protein expression in combination with the sex differences in circulating T may cause sexual differentiation of the mouse cortex/hippocampus.